Accounting controls at the Kelheim Brewery in the seventeenth century: Single entry accounting as fit for purpose - Martin Quinn; Gerhard Kristandl (Essays in Economic & Business History (EEBH), 2021)
Prior to the arguably superior double-entry system of accounting, single-entry accounting was used widely. Extant literature on single-entry accounting suggests it remained in use well after the advent of double-entry, with ease of use cited as a key reason. However, there may be other reasons which have not been revealed in the literature. This study explores how single-entry accounting was utilized at the Kelheim brewery in Bavaria, Germany during the seventeenth century. It finds an organizational field in which single-entry accounting was fit for purpose. Single-entry accounting provided sufficient information and accountability, implying the more sophisticated double-entry accounting system was not used although it was known in Germany at this time .
Keywords: M10; N80; 330; Seventeenth century; brewing; accounting controls; organizational field